A educação infantil inclusiva e a aprendizagem de crianças com deficiência visual - Moraes, Jessica da Silva (Brasil, 2025)
This research aims to understand the teaching and learning process of children with visual impairments in early childhood education. It focuses on describing and analyzing the historical context of the education of visually impaired children, understanding the importance of early stimulation for their learning and analyzing pedagogical processes with a view to the inclusion of visually impaired children in schools. The methodology used is qualitative, based on bibliographical research for the analysis and discussion of the information obtained, and thus understand the importance of diversified and inclusive learning in the lives of all visually impaired children.